Solve for b y=(a+b+c)/6

Math
y=a+b+c6
Rewrite the equation as a+b+c6=y.
a+b+c6=y
Multiply both sides of the equation by 6.
6⋅a+b+c6=6⋅y
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅a+b+c6=6⋅y
Rewrite the expression.
a+b+c=6⋅y
a+b+c=6y
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Subtract a from both sides of the equation.
b+c=6y-a
Subtract c from both sides of the equation.
b=6y-a-c
b=6y-a-c
Solve for b y=(a+b+c)/6

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top